Legalitas Perjanjian Asuransi Melalui Telemarketing Ditinjau Dari Peraturan Otoritas Jasa Keuangan (Pojk) Nomor 1/Pojk.07/2013 Tentang Perlindungan Konsumen Sektor Jasa Keuangan; Studi Kasus: BNI Life - Rahma Dwi Saputri; M Nadratuzzaman Hosen (JOURNAL of LEGAL RESEARCH, 2019)
AbstractInsurance is a willingness to determine the loss as a substitute for large losses that are not yet certain. Along with technological advancement, the insurance industry has begun to develop and the marketing model has also transformed, initially marketing insurance products are only done face-to-face (conventional) method, but now the method was developed by using the telemarketing method. This study aims to determine how the legality of insurance agreements through telemarketing reviewed from Peraturan Otoritas Jasa Keuangan (POJK) Nomor 1/POJK.07/2013 and also to find out the suitability of the insurance agreement through telemarketing according to the principle of consensual in the agreement law at BNI Life. This research uses normative-empirical research and library research by conducting a study of the applicable laws and regulations that support the results of a study. The results of the study show that the insurance offers made by BNI Life were in accordance with those stipulated in POJK 1/2013. However, in practice, the insurance agreement made when making the offer cannot be a perfect agreement, because the insurance agreement through telemarketing by BNI Life does not fulfil the principle of consensual in the agreement law.Keywords: Agreement, Insurance, Telemarketing, Legality